Circulating CD34-positive cells, glomerular filtration rate and triglycerides in relation to hypertension. Issue 1 (November 2015) - Shimizu, Yuji; Sato, Shimpei; Koyamatsu, Jun; Yamanashi, Hirotomo; Nagayoshi, Mako; Kadota, Koichiro; Maeda, Takahiro
Abstract Objective Serum triglycerides have been reported to be independently associated with the development of chronic kidney disease (CKD), which is known to play a role in vascular disturbance. On the other hand, circulating CD34-positve cells, including endothelial progenitor cells, are reported to contribute to vascular repair. However, no studies have reported on the correlation between triglycerides and the number of CD34-positive cells. Since hypertension is well known factor for vascular impairment, the degree of correlation between serum triglycerides and circulating CD34-positve cells should account for hypertension status. Methods We conducted a cross-sectional study of 274 elderly Japanese men aged ≥60years (range 60–79 years) undergoing general health checkups. Results Multiple linear regression analysis of non-hypertensive subjects adjusting for classical cardiovascular risk factors showed that although triglyceride levels (1SD increments; 64 mg/dL) did not significantly correlate with glomerular filtration rate (GFR) (β = −2.06, p = 0.163), a significant positive correlation was seen between triglycerides and the number of circulating CD34-positive cells (β = 0.50, p = 0.004). In hypertensive subjects, a significant inverse correlation between triglycerides and GFR was observed (β = −2.66, p = 0.035), whereas no significant correlation between triglycerides and the number of circulating CD34-positive cells was noted (β = −0.004, p = 0.974). Conclusion Since endothelial progenitor cells (CD34-positive cells) have been reported to contribute to vascular repair, our results indicate that in non-hypertensive subjects, triglycerides may stimulate an increase in circulating CD34-positive cells (vascular repair) by inducing vascular disturbance.